Report on teaching costume design and artistic make-up for the Federal University of Goiás’ Art Direction course during COVID-19 pandemics (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
This report presents a teaching approach adopted for disciplines related to "Costume Design" and " Make-up and Prosthetics". The disciplines were held at the Art Direction course at the Federal University of Goiás. In isolation, it was necessary for students and teachers to adapt quickly to the reality of the moment, which culminated in some quality losses but also enabled good learnings that came to stay. The report presents the initial approaches adopted for each discipline mentioned above and specifies the content of three activities that proved to be very productive because they deal with relevant topics of contemporary and indicates procedures that can be adopted as a creative methodology. The three activities are entitled: “Repetitions, Fractals and Parametrics”, “Material Driven Design” and “Interfaces that Change Perception”. Such contents contribute to the intersection of themes related to characterization and other fields of knowledge such as mathematics, engineering, biology, among others.
Keywords: costume design; remote teaching; contemporary; covid-19